2016
DOI: 10.1093/rpd/ncw019
|View full text |Cite
|
Sign up to set email alerts
|

Patient Exposure Optimisation Through Task-Based Assessment of a New Model-Based Iterative Reconstruction Technique

Abstract: The goal of the present work was to report and investigate the performances of a new iterative reconstruction algorithm, using a model observer. For that, a dedicated low-contrast phantom containing different targets was scanned at four volume computed tomography dose index (CTDIvol) levels on a Siemens SOMATOM Force computed tomography (CT). The acquired images were reconstructed using the ADMIRE algorithm and were then assessed by three human observers who performed alternative forced choice experiments. Nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…MBIR, which may be applied at different strengths, perform noise reduction in both raw data and image domains and incorporate physical models to accurately correct for a variety of image degrading effects [ 13 , 14 ]. Several studies indicate that an increase in the strength of IR allows for larger dose reductions [ 13 , 15 , 16 ]. Evaluations of radiological imaging methods can be performed either by studying their ability to provide correct diagnoses [ 17 ] or by visual assessment of well-defined image quality features (visual grading) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…MBIR, which may be applied at different strengths, perform noise reduction in both raw data and image domains and incorporate physical models to accurately correct for a variety of image degrading effects [ 13 , 14 ]. Several studies indicate that an increase in the strength of IR allows for larger dose reductions [ 13 , 15 , 16 ]. Evaluations of radiological imaging methods can be performed either by studying their ability to provide correct diagnoses [ 17 ] or by visual assessment of well-defined image quality features (visual grading) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, a better model observer software, with sophisticated interfaces and specific setup possibilities, should probably be adopted in future to assist better and predict human observer’s performance. Implementation of a more advanced software, which is beyond the aim of this study, is, however, very complex, as it requires a thorough knowledge of model observer theory, statistics and informatics [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A channelized Hotelling model observer has previously been used to assess the low-contrast detectability in images of an anthropomorphic phantom in computed tomography (5,6) . These studies showed a positive correlation and agreement with human observers in terms of percent correct in 4AFC experiments, and the mathematical model observer was shown to be less time consuming than human observers when performing receiver operating characteristics (ROC) studies.…”
Section: Introductionmentioning
confidence: 99%